Comparison of spark channel expansion in hydrogen, oxygen and nitrogen - Korytchenko, K.V.; Kashanskyi, Yu.V.; Cherkashyn, O.V.; Belyuchenko, D.Yu.; Maksimov, A.V.; Nikorchuk, A.I.; Chernenko, P.V. (Вопросы атомной науки и техники, 2020)
The results of the spark channel expansion simulation in various gases such as hydrogen, oxygen and nitrogen have been presented. Difference in thermodynamic properties of the various gases has been taken into account. Influence of a type of gas on the discharge current, the spark resistance, the energy deposited in the spark and the spark gas-dynamic expansion has been found out. Influence of initial species concentration in mixture of nitrogen, hydrogen and oxygen on detonation initiation by spark discharge has been discussed.